An Empirical Analysis of Substitution Between Engineers and Technicians in Canada - Skolnik, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author analyzes substitution between engineers and technicians through the application of a derived demand equation model to 1961 Census data and concludes that there is considerable substitution between these groups. The conclusion is qualified by noting certain weaknesses of the data. The results should be viewed in the context of the importance of substitution for manpower and educational planning and the lack of empirical study to date.